Aryne-based strategy in the total synthesis of naturally occurring polycyclic compounds. (24th October 2018) - Takikawa, Hiroshi; Nishii, Arata; Sakai, Takahiro; Suzuki, Keisuke
Abstract : This review has outlined the strategies and tactics of using arynes in the total syntheses of polycyclic natural products. Abstract : The total syntheses of polycyclic natural products by exploiting an aryne as the key reactive species are reviewed. A short introduction summarizes the basic reactivities of aryne species as well as the methods for its generation. In the main part, early examples and the recent reports (mainly 2012–present) on the use of arynes in multistep syntheses are described.